Embracing a Multipolar World: Management and Organization Scholars and Varieties of Socialism - Bruton, Garry D.; Li, Jiayi; Gautam, Dhruba Kumar (Journal of Management Studies, 2026)
Abstract Despite the evolution to a multipolar economic world during the past three decades, management and organization scholars around the world still largely employ a capitalist view from the United States as the normal state, with scholars analysing other economic contexts as some variation of such capitalism. Despite the fact that over 43 percent of the world's population lives in nations whose constitutions say the nation is socialist, management and organization scholars appear frozen in time, tied to a historical period when there was largely only one dominant economic model. Our Point is that when communities (nations or individual groups) pursue other economic forms, scholars need to consider that contextual setting, including the socialism, rather than simply assume a typical United States capitalist context as the foundation for research. We identify, define, and illustrate four varieties of socialism in this Point . In turn, we then demonstrate how scholars' understanding of the specific domain of entrepreneurship can be enriched if the socialism of the given context is addressed rather than capitalism assumed. Management and organization scholarship around the world should, moving forward, reflect the dynamics of each unique context, including the respective economic system in that given context, rather than continue to reinforce a United States epistemological hegemony.